2006
DOI: 10.1542/peds.2005-1294
|View full text |Cite
|
Sign up to set email alerts
|

Use of 2-Channel Bedside Electroencephalogram Monitoring in Term-Born Encephalopathic Infants Related to Cerebral Injury Defined by Magnetic Resonance Imaging

Abstract: Bedside EEG measures in term-born encephalopathic infants are related to the severity of cerebral injury as defined by qualitative MRI. A minimum amplitude of <4 microV appears useful in predicting outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…The two machines read similar levels for both the lower and upper borders, with machine B obtaining 3.37 V lower values for the upper margin of aEEG. In comparison to the original Lectromed paper trace, slightly lower borders have also been reported using machine B in humans (39).…”
Section: Discussionmentioning
confidence: 80%
“…The two machines read similar levels for both the lower and upper borders, with machine B obtaining 3.37 V lower values for the upper margin of aEEG. In comparison to the original Lectromed paper trace, slightly lower borders have also been reported using machine B in humans (39).…”
Section: Discussionmentioning
confidence: 80%
“…This agrees with the low FTOE we observed during this period in HIϩVEH. None of HIϩVEH piglets did recover EEG amplitude over 4 V and all of them showed seizure activity, both effects that signal an unfavourable outcome in human newborns (26,27). In contrast, CBD administration led to a significant recovery of amplitude, with six of eight piglets regaining EEG amplitude by more than 4 V at the end of the experiment.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, CBD administration led to a significant recovery of amplitude, with six of eight piglets regaining EEG amplitude by more than 4 V at the end of the experiment. Improvement in aEEG pattern is considered a good predictor of favorable outcome in newborns (26). In addition, only half of HIϩCBD piglets had significant seizures; a similar reduction of seizures occurs in HI piglets in response to high doses of the anticonvulsant topiramate (18).…”
Section: Discussionmentioning
confidence: 95%
“…16 Several studies have shown that 6 to 12 h of life is the time period during which the aEEG background is most valuable. 12,17,18 Sensitivities in these studies range from 91 to 100%, with positive predictive values of B85%.…”
Section: Introductionmentioning
confidence: 99%